Conceptualizing the Digital Value Chain as a Sustainability Strategy in the Local Fashion Industry - Cholifah, Fismayatni; Suhud, Usep; Wibowo, Setyo Ferry (Siber Nusantara Review & Yayasan Sinergi Inovasi Bersama (SIBER), 2025)
This convergence of sustainability imperatives and digital transformation is reshaping the future of the fashion industry, particularly for local micro, small, and medium enterprises (MSMEs). However, the integration of digital value chains into sustainability strategies remains underexplored, especially in emerging economies. This conceptual paper aims to develop a theoretical framework that positions digital value chain innovation as a strategic enabler of sustainable competitiveness in the local fashion industry. Using content analysis on 60 journal articles published between 2012 and 2025, the study identifies dominant variables. Drawing from the domains of digital transformation, green marketing, and customer value theory, the proposed model illustrates how digitalization of core value chain activities—including sourcing, production, promotion, distribution, and after-sales service—can enhance customer-perceived value through transparency, ethical branding, and operational efficiency. The framework highlights how these innovations contribute to long-term brand trust and competitive advantage in sustainability-oriented markets. This paper contributes to the growing body of literature on sustainable digital marketing and offers practical insights for policymakers and fashion entrepreneurs striving for ecological, social, and economic sustainability alongside prevailing analytical methods, including Structural Equation Modeling (SEM) and Multiple Linear Regression.